THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THAT IN MEDIATION BY JOB SATISFACTION VARIABLES IN PT. GYNURA CONSULINDO - Muhammad Tafrizi Priarso; Prastiyo Diatmono; Siti Mariam (Business and Entrepreneurial Review, 2018)
The objective of this research was to determine the factors that influence job satisfaction and its consequences toward employee performance at PT. Gynura Consulindo. Independent variables in this research are transformational leadership style, work motivation and work environment. The intervening variable in this research is job satisfaction and the dependent variable is employee performance.The methodology of this research was descriptive causality designed by testing hypotheses. Data collection uses primary data by distributing questionnaires to employees of PT. Gynura Consulindo. The sample used in this study was 114 respondents from a population of 160 people based on Slovin's calculations. The results of the study showed that the factors of job satisfaction on employee of PT .Gynura consulindo are transformational leadership style, work motivation, and work environmental. Furthermore, job satisfaction has significant impact towards employee performance. It means that, job satisfaction has very dominant role as mediator in employee performance achievement.